Android-Based Waste Education App: An Information Media on Zero-Waste Programs - Muhammad Zamroni Uska; Rasyid Hardi Wirasasmita; Baiq Desi Dwi Arianti; Yosi Nur Kholisho; Muhammad Djamaluddin; Jamaluddin Jamaluddin (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2021)
Zero waste is one of the programs from the government of West Nusa Tenggara Province in Indonesia, where this program aims to provide education about waste to the public so that the waste can be processed or recycled so that it can be useful. Therefore, for the sake of creating a zero waste culture in the community, it is necessary to have media that provide education to the public about this program. The purpose of this article is to discuss the process of developing an Android-based waste education application as a medium of information about zero waste. This study uses the ADDIE model to make this product with five steps, namely analysis, design, development, implementation and evaluation. The data collection technique used was a questionnaire with a Likert scale, and the subjects in this study were the 60 people in the Menceh village. The data analysis technique used is descriptive quantitative. Our findings show that this application (media) is declared very-feasible by material (content) experts with a score of 85% and media (design) experts (83%), and user usability is in the very-high category (83%). So it can be concluded that this application is feasible to use properly, so that users can obtain information about how to manage waste through a zero waste program.